Investigation of the interaction between protein and europium doped polymer. Issue 1 (2nd January 2019) - Hu, Xiaoxi; Tong, Zhangfa; Wang, Yun; Liao, Dankui; Yin, Yanzhen; Wen, Feng
Abstract: The interactions between bovine serum albumin (BSA) and polymer (poly (METAC-co-NIPAm-co-Eu(AA)3Phen), PMNEu) containing rare earth element (Europium) were detailedly investigated by both of experimental techniques, such as fluorescence spectroscopic analysis, zeta-potential characterization, hydrodynamic size measurements and transmission electron microscopy (TEM) observation, and theoretical calculations. As a result, we concluded that PMNEu could interact with BSA through electrostatic force and quench the fluorescence of BSA, which was regarded as the static quenching mechanism. In addition, the binding constant and binding sites number of BSA with PMNEu were calculated, and the distance between PMNEu and BSA was also estimated to be 1.9 nm based on Föster's theory. Furthermore, the two fluorescence peaks of PMNEu at 594 nm and 618 nm were detected, and the density of them increased with the more BSA being added to couple with PMNEu. Additionally, The zeta-potential results confirmed the electrostatic interaction mode between BSA and PMNEu, which was concluded with the previous thermodynamic analysis. At last, the results from the hydrodynamic size measurement had a good agreement with those from the TEM observation about the structure and size variation during the complexation of PMNEu with different concentrations of BSA.